Tools for living a sourcebook of iconic designs for the home - Fiell, Charlotte; Fiell, Peter (London Fiell Publishing, 2010)
Tools For Living' is a book all about 'ultimates' - the ultimate things designed for the home - from chef knives and pots and pans, to door handles and bathroom taps, to home-office furniture and garden tools.
Text in English, French and German.
Keywords: Industrial design -- History -- Catalogs; Furniture design -- History -- Catalogs; Design